A depositional model for hydromagnesite–magnesite playas near Atlin, British Columbia, Canada. Issue 6 (7th June 2014) - Power, Ian M.; Wilson, Siobhan A.; Harrison, Anna L.; Dipple, Gregory M.; McCutcheon, Jenine; Southam, Gordon; Kenward, Paul A.
Abstract: This study formulates a comprehensive depositional model for hydromagnesite–magnesite playas. Mineralogical, isotopic and hydrogeochemical data are coupled with electron microscopy and field observations of the hydromagnesite–magnesite playas near Atlin, British Columbia, Canada. Four surface environments are recognized: wetlands, grasslands, localized mounds (metre‐scale) and amalgamated mounds composed primarily of hydromagnesite [Mg5 (CO3 )4 (OH)2 ·4H2 O], which are interpreted to represent stages in playa genesis. Water chemistry, precipitation kinetics and depositional environment are primary controls on sediment mineralogy. At depth (average ≈ 2 m), Ca–Mg‐carbonate sediments overlay early Holocene glaciolacustrine sediments indicating deposition within a lake post‐deglaciation. This mineralogical change corresponds to a shift from siliciclastic to chemical carbonate deposition as the supply of fresh surface water (for example, glacier meltwater) ceased and was replaced by alkaline groundwater. Weathering of ultramafic bedrock in the region produces Mg–HCO3 groundwater that concentrates by evaporation upon discharging into closed basins, occupied by the playas. An uppermost unit of Mg‐carbonate sediments (hydromagnesite mounds) overlies the Ca–Mg‐carbonate sediments. This second mineralogical shift corresponds to a change in the depositional environment from subaqueous to subaerial, occurring once sediments 'emerged' from the water surface. Capillary action and evaporation draw Mg–HCO3 water up towards the ground surface, precipitating Mg‐carbonate minerals. Evaporation at the water table causes precipitation of lansfordite [MgCO3 ·5H2 O] which partially cements pre‐existing sediments forming a hardpan. As carbonate deposition continues, the weight of the overlying sediments causes compaction and minor lateral movement of the mounds leading to amalgamation of localized mounds. Radiocarbon dating of buried vegetation at the Ca–Mg‐carbonate boundary indicates that there has been ca 8000 years of continuous Mg‐carbonate deposition at a rate of 0·4 mm yr −1 . The depositional model accounts for the many sedimentological, mineralogical and geochemical processes that occur in the four surface environments; elucidating past and present carbonate deposition.